Image Hiding Using Discrete Cosine Transform (Journal of the College of Education for Women, 2019)
Steganography is a mean of hiding information within a more obvious form ofcommunication. It exploits the use of host data to hide a piece of information in such a waythat it is imperceptible to human observer. The major goals of effective Steganography areHigh Embedding Capacity, Imperceptibility and Robustness. This paper introduces a schemefor hiding secret images that could be as much as 25% of the host image data. The proposedalgorithm uses orthogonal discrete cosine transform for host image. A scaling factor (a) infrequency domain controls the quality of the stego images. Experimented results of secretimage recovery after applying JPEG coding to the stego-images are included.